TANGGUNG JAWAB PEMERINTAH TERHADAP PENDIDIKAN ISLAM DALAM MENYONGSONG INDONESIA EMAS 2045 - Fitriani Fitriani; Hasan Basri; Ujang Dedih (Institut Pendidikan Tapanuli Selatan, 2023)
The purpose of this study is to discuss the government's responsibility for Islamic education in welcoming Indonesia Gold 2045. The qualitative research method is in the form of library research. The results of this study illustrate that the government is responsible for Islamic education, this is indicated by the provision of scholarships. Some of the scholarships provided by the government include: the Rising Indonesia Scholarship (BIB) in collaboration with the Education Fund Management Institute (LPDP) to be realized in 2022, 5000 Domestic and International Doctoral Scholarships, Indonesia Smart College Card Scholarship (KIP-K), Islamic Higher Education Affirmation Scholarships (ADIKTIS), Scholarships to study in Egypt, Madrasa Teacher Scholarships, PAI Teacher Scholarships at Schools, Scholarship Program for Students with Achievement (PBSB) which has been running since 2005, Scholarships for Ulama Cadres, and other scholarships. This research concludes that the government, especially the Ministry of Religion is trying to provide educational facilities for Muslims to continue their studies as an effort to prepare Human Resources (HR) who are ready to welcome Indonesia Golden 2045. In addition, education that is built must be based on Islamic education which pays attention to aspects monotheism, morals, physical, intellectual, psychological, social and sexual.